Water-based polyurethane dispersions: Chemistry, Technology and applications - Isabel Fernandes (2013)
Over the past few decades, polyurethane-polyur ea aqueous dispersions (PUDs) have developed a solid reputation for high performance applicati ons, particularly in the field of adhesives and coatings. PUDs are mostly environmentally comp atible products; they are totally devoid or contain only low amounts of volatile organic compounds (VOC). This is an important feature in view of the present environmental policies wher e governments and internal agencies are placing emphasis on developing sustainable processes, improving work conditions and reducing emissions of toxic and polluting substances into the atmosphere. In the past years, our research group has been involved in the development of polyurethane- polyurea aqueous dispersions for two main appli cations (footwear and indirect food contact). With this work we intend to review this theme and describe some of the achieved developments. Characterization of commertial dispersions will be presented and examples of synthesis will be described, following a modified pre-polymer process developded in our group.